Pemahaman Mahasiswa Hukum Terhadap UU ITE Dalam Bermedia Sosial (Studi Pada Mahasiswa Fakultas Syariah UIN Raden Intan Lampung) - Hendriyadi, Hendriyadi; Malik, Anas (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
In the increasingly developed digital era, information technology, particularly the internet and social media, has had a significant impact on people's lives. While it offers ease of interaction and access to information, the rapid development of this technology also brings challenges, such as the rise of cybercrime and the misuse of social media. To address these issues, the Indonesian government enacted Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE), aimed at creating a secure digital environment. However, the implementation of the UU ITE often leads to misunderstandings, particularly among the younger generation, which risks stifling freedom of expression. This study aims to assess the level of understanding of law students regarding UU ITE, especially in the context of social media usage. The research employs a descriptive qualitative approach with data collection methods through questionnaires and in-depth interviews. The respondents in this study are 245 law students from various universities in Lampung. The results show that the majority of students understand UU ITE and social media ethics, but their awareness of the importance of verifying information before sharing news on social media is still low. Their understanding of legal sanctions related to defamation, hoaxes, and hate speech is fairly good, but there is a need to raise awareness about the negative impact of spreading unverified information. This research contributes to the understanding and implementation of UU ITE among law students, as well as the importance of further education on digital responsibility.